QR Code Integrity Verification Based on Modified SHA-1 Algorithm - Rogel Ladia Quilala; Ariel M Sison; Ruji P Medina (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2018)
The modified SHA-1 algorithm was applied in the data integrity verification process of certificates with QR code technology. This paper identified the requirements needed in the certificate verification that uses the modified SHA-1. The application was tested using legitimate and fraudulent certificates. Based on the results, the application successfully generated QR codes, printed certificates, and verified certificates with 100% accuracy. During the trial run of the app, four test cases were seen which involves correct names and QR codes, and three other possible test cases of faking certificates such as modification of the name, regeneration of QR codes using valid hash and a fake name, and modification of the QR code. Although these cases exist, the app successfully verified all thirty certificates correctly. Also, it is noticed that during the scanning, the smartphone camera should be in focus to capture the QR code clearly.